Effects of vaginal cylinder position on dose distribution in patients with endometrial carcinoma in treatment of vaginal cuff brachytherapy - Ozdemir, Yurday; Dolek, Yemliha; Onal, Cem (Journal of Contemporary Brachytherapy, 2017)
Purpose: To investigate the impact of different cylinder positions on dosimetry of critical structures in patients with endometrial carcinoma undergoing three-dimensional image-based vaginal cuff brachytherapy (VCB). Material and methods: We delivered VCB at a dose of 4 Gy to a depth of 5 mm in the vaginal cuff of 15 patients using three different cylinder positions (neutral [N], parallel [P], and angled [A]) according to the longitudinal axis of the patient. We analyzed the dose-volume distribution and volumetric variability of the rectum and bladder. We converted the total doses to equivalent doses in 2 Gy (EQD 2 ) using a linear-quadratic model (a/b = 3 Gy). Results : The mean rectum volume for the N, P, and A positions was 68.2 ± 22.7 cc, 79.3 ± 33.7 cc, and 74.2 ± 29.6 cc, respectively. The mean rectum volume for the P position was significantly larger than that for the N position (p = 0.03). Relative to the N position, the A position resulted in a lower total EQD 2 in the highest irradiated 2 cc (D 2cc ; p = 0.001), 1 cc (D 1cc ; p = 0.004), and 0.1 cc (D 0.1cc ; p = 0.047) of the rectum. Similarly, the P position resulted in a lower EQD 2 in the D 2cc (p = 0.018) and D 1cc (p = 0.024) of the rectum relative to the N position. In the bladder, the P position resulted in a higher EQD 2 in the D 2cc relative to the N position (p = 0.02). There was no dosimetric difference between the P and A positions in either the rectum or the bladder. Conclusions : Vaginal cuff brachytherapy in the P and A positions is significantly superior to that in the N position in terms of rectum dosimetry. The bladder dose in the N position is considerably lower than that in the other positions.